Strategy of Dakwah in War: A Study of Muhammad Al-Fatih's Conquest of Constantinople - Firda Amalia Fatma Ahyani (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to analyze Muhammad Al-Fatih's Da'wah Strategy when conquering Constantinople in 1453, which was one of the important events in the history of Islamic Civilization and world geopolitics. In expanding Islamic territory, Muhammad Al-Fatih faced many challenges, including the very strong defense of the Byzantine Empire. To understand the role of da'wah strategies in the campaign to conquer Constantinople, this research uses qualitative methods in the form of library research. Studies that consider a variety of strategies, including military, diplomatic, propaganda, and psychological strategies. The research results show that Al-Fatih not only used military force to conquer Constantinople but also used da'wah strategies to achieve his goals. Muhammad Al-Fatih's missionary strategy included using Islamic literature and thought to motivate his troops, gaining support from ulama and religious scholars, as well as propaganda to make the enemy have a good perception. This research provides insight into the role of da'wah strategies in the success of military campaigns and how these strategies contributed to Muhammad Al-Fatih's conquest of Constantinople. These findings may inspire further research into the role of da'wah strategies in Islamic history and other important historical events.